(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Dementia is one of the major health issues in the elderly. It is the fifth leading cause of death and a primary cause of disability and dependence in older adults. Hypertension, particularly in the elderly, is a cardiovascular risk factor associated with stroke, lacunar infarction, white matter disease of the brain, cognitive impairment, and vascular dementia. Therefore, in the Department of Cardiology at Thong Nhat Hospital, we conducted a survey on the prevalence and factors related to dementia in elderly patients with hypertension. Objective: To estimate prevalence of dementia and related factors among elderly patients with hypertension admitted to the Cardiology Department of Thong Nhat Hospital. Methods: The study will include all elderly patients diagnosed with hypertension at the Cardiology Department of Thong Nhat Hospital from November 2023 to August 2024. Results: In a study of 185 elderly patients with hypertension, the prevalence of dementia was 16.8%, while 83.2% did not have dementia. There was a statistically significant relationship between age group, IADL, ADL, and CFS status with dementia, with p < 0.05. Patients with frailty (CFS > 4) had a significantly higher risk of dementia compared to those without frailty (CFS ≤ 4). Additionally, the risk of developing dementia increased with age, which was statistically significant (p < 0.001), particularly in the group aged 80 and older. Conclusion: Elderly patients with hypertension, particularly those aged 70 and older, have a higher risk of developing dementia. The MMSE scores decrease with the level of frailty. This highlights the importance of using the MMSE as a primary assessment tool for diagnosing and monitoring dementia.